Comprehensive performance study on reflux solar methanol steam reforming reactor for hydrogen production. (8th January 2023) - Zhang, Tong; Tang, Xin-Yuan; Yang, Wei-Wei; Ma, Xu
Abstract: In this paper, a reflux solar methanol steam reforming reactor (SMSRR) system is proposed for efficient solar thermal hydrogen produced. A two-dimensional (2D) axisymmetric model is used to compare the comprehensive performance of three different SMSRRs: no reflux tube (SMSRR0), flow from the inside of the reflux tube to the outside (SMSRR1) and flow from the outside of the reflux tube to the inside (SMSRR2). The results showed that the reflux SMSRR uses the heat of the fluid at the outlet to further provide the reaction heat, which greatly reduces the outlet temperature, thereby improving the overall performance of the SMORE. By optimizing the diameter of the reflux tube and the operating conditions, the energy conversion rate can be increased by 19.5%, and the temperature distribution coefficients can be increased by 1.89% while the methanol conversion is increased by 6.43%, and the hydrogen yield is increased by 5.96%. Highlights: A new solar receiver-reactor of reflux structure is proposed. A three-dimensional comprehensive model was established for solar receiver-reactors with secondary reflection. . The optimized reflux reactor greatly reduces ΔT io, thereby improving the energy conversion efficiency. The reflux structure in the optimized systems enables the reactor to obtain better uniformity of the temperature field.